Magnetic resonance imaging based muscle strain rate mapping during eccentric contraction to study effects of unloading induced by unilateral limb suspension - Sinha, Usha; Malis, Vadim; Csapo, Robert; Narici, Marco; Sinha, Shantanu (European journal of translational myology, 2020)
Age- and disuse- related loss of muscle force is disproportionately larger than the loss of muscle mass. Earlier studies reported that comparing concentric and eccentric contractions, there is a significant age-related decrease in force only in concentric contractions. Magnetic Resonance Imaging enables mapping of muscle deformation and has been used to study isometric but not eccentric contractions. We report MRI based strain rate mapping of the medial gastrocnemius in subjects pre- and post-unloading induced by Unilateral Limb Suspension. In contrast to isometric contraction, no difference in strain rate indices were observed post-unloading, in conformance with preserved force during eccentric contractions.